Effect of a bacteriocin-producing strain of Streptococcus sobrinus on infection and establishment of Streptococcus mutans on tooth surfaces in rats - Kitamura, K; Masuda, N; Kato, K; Sobue, S; Hamada, S (Oral microbiology and immunology, 1989)
The effect of bacteriocin produced by Streptococcus sobrinus MT6223 on infection and establishment of Streptococcus mutans MT6222 was studied in specific pathogen-free rats. These strains were isolated from a carious lesion of a single subject. S. mutans MT6222 was found to be susceptible to the growth inhibitory action of S. sobrinus MT6223. When simultaneously inoculated into the oral cavity of rats, even a small inoculum (10(5) CFU) of S. sobrinus MT6223 completely inhibited colonization of S. mutans MT6222 on the tooth surface. Also, S. sobrinus MT6223 eliminated S. mutans MT6222 when MT6223 (10(8) CFU) was inoculated 2 days after the inoculation of 10(8) CFU cells of MT6222. Similar results were obtained in dental plaque samples from the tooth surface and the fissures of the upper molars at the end of the experiment. However, when S. sobrinus MT6223 (10(8) CFU) was inoculated 2 weeks after the inoculation of S. mutans MT6222 (10(8) CFU), MT6223 coexisted with MT6222. However, the plaque samples showed that MT6223 inhibited the establishment of MT6222 on smooth surfaces, but not in fissures. In addition, MT6223 protected against subsequent infection with MT6222. However, a nonbacteriocinogenic mutant of S. sobrinus MT6223 did not inhibit the infection and establishment of S. mutans MT6222.